The role of oral traditions in african history - King, Monica Dorothy (Midlands State University, 2015)
Colonial historians writing on Africa believed that before colonization, Africa had no history. Whenever they wrote about Africa, they wrote own imaginations with no respect for the African past. Africans were less or never consulted in the making or remaking of their history. Their past was therefore left uncaptured because historians could not trust African's word of mouth, which they labelled as superstitious, biased and lacking evidence. I argue for a reconstruction of pre-literate African history from oral traditions. Historical poems and songs that relate to events and depict society's politics and social values must be revisited. Chiefs' genealogies and lists of place names that facilitate the study of migrations, demography and political developments of past societies, are more important now than ever because of conflicts tearing Africa apart. Tales reflecting milestones and religions must be understood in the way they contribute to national stability and identity in contemporary Africa.